Krisis Kelembagaan Pariwisata: Studi Kasus Kampung Susu Lawu, Magetan, Jawa Timur - Arandahana, Herafani (Gadjah Mada Journal of Tourism Studies, 2024)
In the tourist system, organizational structures have a crucial part in managing human resources, sustainability planning, and handling management. To ensure the sustained existence of the tourism industry, it is necessary to investigate the phenomena of deteriorating organizations in the sector to determine its roots and identify remedies. This study aimed at evaluating the current state of the Pokdarwis Pesona Singo Langu organization in Kampung Susu Lawu and determining the elements that have weakened it and impeded its efficacy. Using descriptive qualitative analysis, this research collected data from community members, stakeholders, and the chairman of Pokdarwis Pesona Singo Langu through observation and interviews. Three organizational components goals, functions, and formation were the main subjects of the analysis. The findings showed that the goal element has been successfully attained because of the clear legal status. However, there were deficiencies in the goal element. A lack of empathy from the community and the top-down approach to governance and operationalization were two main factors that are undermining the organization. The formation of newly created organizations by younger organizations, the dynamics of the political year, and a lack of coordination and communication were examples of external variables. If corrective action is not done quickly, this phenomenon is likely to set off a wider chain reaction.